New fundamental parameters for the inner disk open cluster Lyngå 11 - Piatti, Andres Eduardo (2006)
We have obtained CCD BVIKC photometry down to V 21.5 for the open cluster Lynga˚ 11 and its surrounding field. This previously unstudied object appears to be rich and highly absorbed. A cluster angular radius of 4.50 ± 0.50 , equivalent to (3.0 ± 0.3) pc, is estimated from star counts in 100-pixel a side boxes distributed throughout the whole observed field. Our analysis suggests that Lynga˚ 11 is moderately young and probably of solar metallicity. Adopting the theoretical metal content Z = 0.02, which provides the best global fit, we derive an age of (630 ± 70) Myr. Simultaneously, colour excesses E(B V) = 0.70 and E(V I) = 0.85 and an apparent distance modulus V MV = 14.0 are obtained. These results place Lynga˚ 11 at a distance of (2.3 ± 0.5) kpc from the Sun and 6.5 kpc from the Galactic centre. The properties of a sample of clusters aligned along the line-of-sight of Lynga˚ 11 are examined as well.